Transcultural adaptation, content, and internal structure validity evidence of the perceived efficacy and goal setting system – 2 edition for Brazilian children - Nobre, Glauber Carvalho; Gonçalves Duarte, Marcelo; da Silva Ramalho, Maria Helena; Flores Sartori, Rodrigo; Schmitt Marinho, Nádia Fernanda; André Aires Soares, Ívina; Valentini, Nadia Cristina (Frontiers in Psychology, 2023)
Aim The aim was to investigate the validity of evidence of the Perceived Efficacy and Goal Setting System second edition for Brazilian children. Methods 258 children participated, both sexes (n = 133 girls; 51.6%), 5 to 9 years old (total sample Mage = 7.1, SD = 1.4), from four regions of Brazil. The Perceived Efficacy and Goal Setting System – second edition, was used. Results Experts showed agreement about the high clarity and practical pertinence of the items (content validity coefficient from 98.4 to 100%; Gwet’s agreement coefficient from 0.85 to 1.00, p < 0.001). Confirmatory factorial analysis showed adequate adjustment indexes (RMSEA [0.048, 90% C.I. = 0.043 to 0.053], SRMR [0.243], CFI [0.91], RNI [0.91], TLI [0.91], ꭓ2/df [1.962]). The multigroup analysis showed configural, metric and scalar invariance of two models for gender (CFI = 0.97; RMSEA, [90%C.I.] = 0.05 [0.03 to 0.07]; metric: ΔRMSEA = 0.001; scalar: ΔRMSEA = −0.004) and age band (5–7 years-old and 8–9 years-old; CFI = 0.94; RMSEA, [90%C.I.] = 0.05 [0.03 to 0.07]; metric: ΔRMSEA = 0.002; scalar: ΔRMSEA = 0.010). The Heterotrait-Monotrait ratio test showed adequate discriminant validity among three dimensions (self-care and productivity [value = 0.76]; self-care and leisure [value = 0.57], productivity and leisure [value = 0.76]). Alpha for polychoric correlations showed an adequate internal consistency for all items and total scale (all α values >0.70). Composite reliability (Self-care = 0.8; Productivity = 0.81; Leisure = 0.8) reinforce evidence about reliability. Percentage agreement showed adequate item-level test-retest reliability (values between 76 and 92%). Conclusion This scale showed adequate content and internal structure validity evidence to assess the perceived self-efficacy for Brazilian children.